Get Career Fit, 2nd Edition - Gibbings, Michelle (Be your best., 2019)
Future-proof your career and plan your leap forward Gone are the days of slowly making your way up the corporate ladder to retirement. Now, with the rise of freelancing and the gig economy, the workplace is becoming more flexible and independent - which can leave hardworking people scrambling to find a way to stay relevant. Author Michelle Gibbings addresses your worries and gives you a way forward. This book sheds light on what you can do to reignite, reshape and liberate your career and offers a fool-proof plan for getting your career back on track. With Get Career Fit , you can build a career ready for any change the future may bring.